Unveiling IT Governance Effectiveness in e-Puskesmas Using COBIT 2019 - Sumardiono Sumardiono; Supardi Supardi; Suci Lailla Fitriani; Wiwit Priyadi; Norhafizah Ismail; Riska Suryani (Scientific Journal of Informatics, 2026)
Purpose: This study aims to evaluate the effectiveness of IT governance implementation in the e-Puskesmas system at Pengasinan Community Health Center, Bekasi City, using the COBIT 2019 framework. The research focuses on identifying the capability level and governance gaps to ensure risk management and IT service delivery align with institutional objectives. Methods: The study employs a mixed-method approach combining qualitative interviews and quantitative questionnaires. Two COBIT 2019 domains—APO12 (Managed Risk) and DSS02 (Managed Service Requests and Incidents)—were analyzed using capability level measurements and GAP analysis to determine performance alignment with governance standards. Result: The findings reveal that e-Puskesmas achieved a high capability level, with 96.88% for APO12 and 90.47% for DSS02. Despite this success, several weaknesses were identified, including delays in patient registration, data confidentiality issues, and service disruptions. The study provides strategic recommendations to enhance user training, strengthen data security, and implement continuous risk management. Novelty: This research presents one of the first applications of COBIT 2019 in evaluating IT governance for public healthcare systems in Indonesia. It demonstrates how COBIT can serve as a practical tool for assessing digital health governance maturity, ensuring data integrity, and supporting the sustainable transformation of healthcare services.